Philip L. Geyelin papers - Geyelin, Philip L.; Geyelin, Philip L.
Correspondence, interviews, writings, reports, notes and notebooks, research material, transcripts of broadcasts, congressional hearing records and other government documents, press releases and statements, clippings, photographs, and other papers relating primarily to Geyelin's career as a reporter and editorial page editor covering foreign policy issues for the Wall Street Journal and later the Washington Post. Subjects include the Middle East, the Vietnam War, and individuals such as Zbigniew Brzezinski, Clark M. Clifford, Arthur J. Goldberg, Richard Helms, Townsend Hoopes, Henry Kissinger, Robert S. McNamara, John N. Mitchell, William P. Rogers, W.W. Rostow, Dean Rusk, Bromley K. Smith, and John Paul Vann. Also includes material pertaining to his book, Lyndon B. Johnson and the World (1966), and his writings on Hussein, King of Jordon, and Vietnam War veterans; service as in the U.S. Marine Corps in the Pacific Area during World War II; work for the U.S. Central Intelligence Agency; and the Geyelin family.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Journalist. Full name: Philip Laussat Geyelin. Born, 1923; died, 2004.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brzezinski, Zbigniew, -- 1928-; Clifford, Clark M., -- 1906-1998.; Goldberg, Arthur J; Helms, Richard; Hoopes, Townsend, -- 1922-; Hussein, -- King of Jordan, -- 1935-1999.; Johnson, Lyndon B. -- 1908-1973.; Kissinger, Henry, -- 1923-; McNamara, Robert S., -- 1916-2009.; Mitchell, John N. -- 1913-1988.; Rogers, William P. -- 1913-2001.; Rostow, W. W. -- 1916-2003.; Rusk, Dean, -- 1909-1994.; Smith, Bromley K; Vann, John Paul; Geyelin family; United States. -- Central Intelligence Agency; United States. -- Marine Corps; Wall Street journal; Washington post; American newspapers; Veterans -- United States; Vietnam War, 1961-1975.; World War, 1939-1945 -- Pacific Area; Middle East -- Foreign relations -- United States; United States -- Foreign relations -- 20th century; United States -- Foreign relations -- Middle East; United States -- Politics and government -- 1963-1969.; Vietnam -- History -- 1945-1975.; Vietnam -- History -- 1945-1975 -- Veterans; Journalists